Modelling nitrogen flows in peri-urban vegetable field plots in Nanjing, China - Berg, Josefin (2005)
Many parts of China are going through a rapid development and urbanization resulting in various environmental impairities. The Yangtze Delta Region surface water bodies are affected by eutrophication, partly caused by diffuse losses from agriculture. In this study, nitrogen, and to some extent also phosphorus, flows and losses from two plots in an intensively cultivated vegetable field in a peri-urban area of Nanjing, with a high input of organic fertilizer, were analysed by the use of the field-scale simulation model GLEAMS. The GLEAMS model was parameterized and calibrated against measurements of soil water and nitrogen content in two plots. A scenario with a reduced input of nitrogen was then simulated.